The problems of creating the history of literary criticism and its scientific-methodological bases (Eurasian Journal of Philology Science and Education, 2018)
In this article the history of Kazakh literary criticism, peculiar features and interactions of the conceptas «literary criticism», «literature studies» are considered. Analysis of the significance of some arguablenotions and terms of Criticism.The author tried to solve some problems that still create disagreements between scientists and literary criticizers in the world. The opinions about the criticism of the literature written by Kazakh criticscientists and researches of topical issues of criticism have been analyzed, according to modern requirements they were evaluated by increasing knowledge of the literary-aesthetic point of view. The researchworks of far and near foreign scientists were considered. The conclusions about literary criticism whichKazakh readers need, much information are recommended.The purpose of determining the national and regional features of literary criticism, its aims andboundaries, its place which are engaged in the literary process are also considered.